Investigation on structural and magnetic properties of Al3+ and Ce3+ doped hexaferrites. (2020) - Venkatesh, G.; Subramanian, R.; Satish Kumar, T.; Abuthakir, J.; John Berchmans, L.; Sethupathi, K.
Abstract: Hard magnetic ferrites or Hexa ferrites (AB12 O19, A-Ba, Sr, Ca, Pb) are widely used as permanent magnets, in refrigerator seal gaskets, microphones, and speaker gaskets. They can also be used in small motors for cordless appliances and portable magnetic storage devices. In the present research, Al and Ce doped hexaferrites (AB12 O19 ) were chosen and synthesized by combustion technique using the precursors (Sr(NO3 )2, Ba(NO3 )2, Ca(NO3 )2, Fe(NO3 )3, Al(NO3 )3, Ce(NO3 )3 ) and fuels (C6 H8 O7, C12 H22 O11 ). The prepared powder was calcined at different temperature (800 °C, 900 °C, 1100 °C) for 12 h. Phase identification was done by using X-Ray Diffraction (XRD) technique by which phases were confirmed and also the morphological behavior was studied by using Scanning Electron Microscopy (SEM). Elemental analysis was done by using Energy Dispersive Spectroscopy. The intrinsic magnetic properties were studied by using Vibrating Sample Magnetometer, and the hexaferrites are found to be affected by partial substitution of Sr and Fe sites by rare earth elements (RE 3+ ) and non-magnetic trivalent Al 3+ ions respectively, and it is same in case of BaFe12 O19 and CaFe12 O19 . The insertion of Ce 3+ and Al 3+ into hexagonal lattice enhances the coercivity due to increase in magneto-crystalline anisotropy or grain refinement. Thus, the hexaferrites are doped by Ce and Al to achieve Sr0.9 Ce0.1 Fe10 Al2 O19, Ba0.9 Ce0.1 Fe10 Al12 O19, Ca0.9 Ce0.1 Fe10 Al12 O19 .